A Tongue Lesion as a Sign of a Systemic Disease - Chrysoula I. Liakou; Joan Koh; Antonios Tsimpidakis; Katrina Rios; Charalabos Paskalis; Athanasios Pipilis; Dimitrios Kantianis; Thomas Georgiadis; Evangelia Razis (Case Reports in Medicine)
Amyloidosis is the extracellular fibril deposition of a variety of proteins, many of which circulate as plasma ingredients. It is a disease difficult to identify due to its nonspecific symptoms and manifestations. Amyloidosis of the tongue, either isolated or part of the systemic disease, is rare and its features resemble those of a tumor. We report the case of a patient with amyloidosis who presented with a tongue lesion, weakness, nonspecific arthritis, and dyspnea on exertion that resulted in multiorgan system failure.